When Do Banks Take Equity in Debt Restructurings? - James, Christopher (Review of Financial Studies, 1995)
This article examines the conditions under which bank lenders make concessions by taking equity in financially distressed firms. I show that the role banks play in debt restructurings depends on the financial condition of the firm, the existence of public debt in the firm's capital structure and the ability of public debt to be restructured. Empirically, I find that for firms with public debt outstanding, banks never make concessions unless public debtholders also restructure their claims. When banks do take equity, on average they obtain a substantial proportion of the firm's stock, and they maintain their position for over two years.